China's Foreign Aid and Government-Sponsored Investment Activities Scale, Content, Destinations, and Implications - Wolf, Jr (RAND Corporation, 2013)
With the world's second largest economy, China has the capacity to engage in substantial programs of development assistance and government investment in any and all of the emerging-market countries. RAND researchers assessed the scale, trends, and composition of these programs in 93 countries in six regions: Africa, Latin America, the Middle East, South Asia, Central Asia, and East Asia.